the 7th term of an A.P.is -4 and its 13th term is -16 find the A.P .?
Answers
Answered by
3
(a+6d)=7th term
(a+6d)=-4 & (a+12d)=-16
now solve the equations you will get
-6d=12
d=-2
putting the value of d in any equation
we get. a=8
Now apply the formula
a+(n-1)×d
so A.P=8,6,4,2,0,-2,-4,-6,-8,-10,-12,-14,........ and so on
Please Mark this answer Brainliest
(a+6d)=-4 & (a+12d)=-16
now solve the equations you will get
-6d=12
d=-2
putting the value of d in any equation
we get. a=8
Now apply the formula
a+(n-1)×d
so A.P=8,6,4,2,0,-2,-4,-6,-8,-10,-12,-14,........ and so on
Please Mark this answer Brainliest
Answered by
2
HLO MATE ✋✋
Simran Here!!!!
Here is Ur Answer _________
________________________________⭐⭐⭐
![Given \: that : \: \\ \\ 7th \: term \: = - 4 \\ a + 6d = - 4 = = > (1) \\ \\ 13th \: term \: = - 16 \\ a + 12d = - 16 = = > (2) \\ \\ Now ,\: solve \: the \: equation \: (1) \: and \: (2) \\ \\ From \: eq.(1) \\ a + 6d = - 4 \\ a = - 4 - 6d \\ \\ Putting \: \: the \: value \: of \: a \: in \: eq.(2) \\ a + 12d = - 16 \\ = > ( - 4 - 6d) + 12d = - 16 \\ = > 6d = - 12 \\ = > d = - 2 \\ \\ Putting \: the \: value \: of \: "d "\: in \: eq.(1) \\ = > a = - 4 - 6d \\ = > a = - 4 - 6(-2) \\ = > a = 8\\ \\ So ,\: First \: term \: is \: 8 \: \\ Common \: difference \: =- 2 Given \: that : \: \\ \\ 7th \: term \: = - 4 \\ a + 6d = - 4 = = > (1) \\ \\ 13th \: term \: = - 16 \\ a + 12d = - 16 = = > (2) \\ \\ Now ,\: solve \: the \: equation \: (1) \: and \: (2) \\ \\ From \: eq.(1) \\ a + 6d = - 4 \\ a = - 4 - 6d \\ \\ Putting \: \: the \: value \: of \: a \: in \: eq.(2) \\ a + 12d = - 16 \\ = > ( - 4 - 6d) + 12d = - 16 \\ = > 6d = - 12 \\ = > d = - 2 \\ \\ Putting \: the \: value \: of \: "d "\: in \: eq.(1) \\ = > a = - 4 - 6d \\ = > a = - 4 - 6(-2) \\ = > a = 8\\ \\ So ,\: First \: term \: is \: 8 \: \\ Common \: difference \: =- 2](https://tex.z-dn.net/?f=Given+%5C%3A+that+%3A+%5C%3A+%5C%5C+%5C%5C+7th+%5C%3A+term+%5C%3A+%3D+-+4+%5C%5C+a+%2B+6d+%3D+-+4+%3D+%3D+%26gt%3B+%281%29+%5C%5C+%5C%5C+13th+%5C%3A+term+%5C%3A+%3D+-+16+%5C%5C+a+%2B+12d+%3D+-+16+%3D+%3D+%26gt%3B+%282%29+%5C%5C+%5C%5C+Now+%2C%5C%3A+solve+%5C%3A+the+%5C%3A+equation+%5C%3A+%281%29+%5C%3A+and+%5C%3A+%282%29+%5C%5C+%5C%5C+From+%5C%3A+eq.%281%29+%5C%5C+a+%2B+6d+%3D+-+4+%5C%5C+a+%3D+-+4+-+6d+%5C%5C+%5C%5C+Putting+%5C%3A+%5C%3A+the+%5C%3A+value+%5C%3A+of+%5C%3A+a+%5C%3A+in+%5C%3A+eq.%282%29+%5C%5C+a+%2B+12d+%3D+-+16+%5C%5C+%3D+%26gt%3B+%28+-+4+-+6d%29+%2B+12d+%3D+-+16+%5C%5C+%3D+%26gt%3B+6d+%3D+-+12+%5C%5C+%3D+%26gt%3B+d+%3D+-+2+%5C%5C+%5C%5C+Putting+%5C%3A+the+%5C%3A+value+%5C%3A+of+%5C%3A+%22d+%22%5C%3A+in+%5C%3A+eq.%281%29+%5C%5C+%3D+%26gt%3B+a+%3D+-+4+-+6d+%5C%5C+%3D+%26gt%3B+a+%3D+-+4+-+6%28-2%29+%5C%5C+%3D+%26gt%3B+a+%3D+8%5C%5C+%5C%5C+So+%2C%5C%3A+First+%5C%3A+term+%5C%3A+is+%5C%3A+8+%5C%3A+%5C%5C+Common+%5C%3A+difference+%5C%3A+%3D-+2)
So, a2 = a+ d
=> a2 = 8-2
=> a2 = 6
a3 = a2 + d
=> a3 = 6 +( -2)
=> a3 = 4
We get A.P. : 8 ,6,4,2,0,-2,-4....
_______________________________⭐⭐⭐
HOPE IT HELPS UH ☺
^_^
❤BE BRAINLY❤
Simran Here!!!!
Here is Ur Answer _________
________________________________⭐⭐⭐
So, a2 = a+ d
=> a2 = 8-2
=> a2 = 6
a3 = a2 + d
=> a3 = 6 +( -2)
=> a3 = 4
We get A.P. : 8 ,6,4,2,0,-2,-4....
_______________________________⭐⭐⭐
HOPE IT HELPS UH ☺
^_^
❤BE BRAINLY❤
Similar questions